2022
DOI: 10.18196/jbti.v13i2.14458
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Environment, Social and Governance Disclosure on Firm Value

Abstract: This study aims to determine the environmental, social, and governance of the firm value in this study are all companies listed on the Indonesia Stock Exchange from 2016-2020. The determination of the sample in this study used purposive sampling with the number of samples used by as many as 27 companies during the year. a period of 5 consecutive years of observation so that the total sample obtained is 135. This study uses Stata 14, the analytical technique used is panel data regression analysis. The results s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 16 publications
2
2
0
Order By: Relevance
“…Based on the results of the hypothesis test, it was found that environmental disclosure has a significant positive influence on the value of the company. This is in line with research conducted by Kamilla (2020), Anggreni et al (2022), Fitri et al (2019, Sundari and Setiany (2021), Suretno et al (2022) which stated that corporate environmental disclosure has a positive influence on firm value. Muslichah (2020) stated that environmental disclosure has a significant influence on company performance.…”
Section: Environmental Disclosuresupporting
confidence: 89%
“…Based on the results of the hypothesis test, it was found that environmental disclosure has a significant positive influence on the value of the company. This is in line with research conducted by Kamilla (2020), Anggreni et al (2022), Fitri et al (2019, Sundari and Setiany (2021), Suretno et al (2022) which stated that corporate environmental disclosure has a positive influence on firm value. Muslichah (2020) stated that environmental disclosure has a significant influence on company performance.…”
Section: Environmental Disclosuresupporting
confidence: 89%
“…The ESG ratings was found to have a positive and significant relationship with the firm value in Aydoğmuş et al (2022) study on 5000 public companies worldwide. Similar result also found in Suretno et al (2022) on 27 public companies in Indonesia for the 2016-2020 data period. In contrast, research on 52 public companies in Indonesia for the 2015-2019 data period by Lubis and Rokhim (2021) shows a negative relationship between ESG ratings and firm value.…”
Section: Introductionsupporting
confidence: 85%
“…The practice of corporate governance in the company is indeed implemented, but its implementation is not entirely by the principles of corporate governance transparency, accountability, responsibility, independence, and fairness. In other words, the practice of corporate governance is carried out by the company only as a formality or fulfilment of the company's obligations towards the regulations set by the government (Suretno et al, 2022). This phenomenon indeed will reduce investor trust in governance disclosure.…”
Section: Resultsmentioning
confidence: 99%